THE IMPROVEMENT OF SKILLS IN DEFINING AND TAKING CONCLUSION IN SOLUBILITY AND SOLUBILITY PRODUCT THROUGH ADVANCE ORGANIZER LEARNING MODEL - janwarsam putra panggar; noor fadiawati; chansyanah diawati (Jurnal Pendidikan dan Pembelajaran Kimia, 2012)
The aim of this research was to describe effectiveness of advance organizer learning model to improving skills of defining and taking conclusion skill on the matter of  solubility and solubility product. The subject in this research were students in classroom XI IPA3 SMA N 7 Bandar Lampung. This research used a pre-experiment method with One Group pretest-posttest design. The effectiveness of advance organizer learning model was measured by the n-gain average. The research results showed that the average of n-gain values of skills in defining and drawing conclusions were 0.48 (middle category) and 0.54 (middle ca-tegory) respectively. This shows that (1) a model of advance organizer is effective to enhance the skill of defining in the medium category (2) a model of advance organizeris effective to enhance the skill of taking conclusion in the medium category.Keywords: advance organizer, skills in defining and taking conclusion